Deuterium‐labeled phylloquinone fed to α‐tocopherol‐injected rats demonstrates sensitivity of low phylloquinone‐containing tissues to menaquinone‐4 depletion. Issue 8 (14th July 2014) - Farley, Sherry M.; Leonard, Scott W.; Stevens, Jan F.; Traber, Maret G.; Traber, Maret G.
<x xml:space="preserve">Abstract</x> Scope The influence of excess α‐tocopherol (α‐T) on tissue depletion of phylloquinone (PK) and menaquinone‐4 (MK‐4) was evaluated. Methods and results Rats (n = 5 per group) were fed deuterium‐labeled PK (2 μmol/kg diet) for 17 days, thereby labeling the conversion from deuterium‐labeled PK to d4‐MK‐4. Then they were injected subcutaneously daily for the last 7 days with saline, vehicle, or α‐T (100 mg/kg body weight). α‐T injections (i) increased α‐T concentrations by tenfold in liver, doubled them in plasma and most tissues, but they were unchanged in brain; (ii) increased the α‐T metabolite, carboxyethyl hydroxychromanol (α‐CEHC) concentrations: >25‐fold in liver and kidney, tenfold in plasma and lung, and 50‐fold in heart; brain contained detectable α‐CEHC (0.26 ± 0.03 nmol/g) only in α‐T‐injected animals; and (iii) depleted most tissues' vitamin K. Compared with vehicle‐injected rats, brains from α‐T rats contained half the total vitamin K (10.3 ± 0.5 versus 21 ± 2 pmol/g, p = 0.0002) and one‐third the d4‐MK‐4 (5.8 ± 0.5 versus 14.6 ± 1.7 pmol/g, p = 0.0002). Tissues with high PK concentrations (liver, 21–30 pmol/g and heart, 28–50 pmol/g) were resistant to K depletion. Conclusion We propose that α‐T‐dependent vitamin K depletion is likely mediated at an intermediate step in MK‐4 production; thus, tissues with high PK are unaffected.